Applications of Cu@C Nanoparticles in New Dye-Sensitized Solar Cells. (6th April 2009) - Liao, Chang-Yu; Wang, H. Paul; Chen, F.-L.; Huang, C.-H.; Fukushima, Y.
Abstract : To enhance the efficiency of a newly developing dye-sensitized solar cell (DSSC), the Cu@C (Cu size = 7 and 20 nm) core-shell nanoparticles-dispersed molten salt-conjugated electrolyte has been studied. Experimentally, the efficiencies (η ) of the DSSC are in the range of 2.70–4.09% with a short-circuit photocurrent density (J SC ) of 5.775–9.910 mA/cm 2 . Interestingly, it is found that dispersion of 1% of the Cu@C (Cu size = 7 nm) nanoparticles in the molten salt-(1, 2-dimethyl-3-propylimidazolium iodide (DMPII)) conjugated electrolyte results in an enhancement (about 11%) of the η (4.06%). Greater fractions (3–10%) of the Cu@C nanoparticles dispersed in the molten salt cause a poor performance (lower J SC and η ) of the DSSC possibly due to interference of the internal electron transportation routes in the DSSC by oxidation of Cu with I 2 originally in the electrolyte.